Strengthening the PCA organization's awareness of the importance of mental health - Adhianty Nurjanah; Sri Nabawiyati Nurul Makkiyah; Riski Apriliani (Universitas Muhammadiyah Magelang, 2024)
Aisyiyah Ngampilan Branch, committed to women's empowerment, initiated a mental health program in response to Indonesia's high rate of mental disorders. This program aimed to enhance administrators' awareness and understanding of mental health, equipping them to empower the community in this area. The program was implemented through socialization methods. Results showed a significant increase in administrators' knowledge of mental health and stress management, with success rates of 88% and 85%, respectively. Additionally, the branch received a sound system to strengthen its infrastructure. This program benefits both administrators and the broader community. By understanding mental health and stress management, women can better navigate life's challenges, both within families and organizations. The program's integration of Islamic values aligns with community needs.